Costs and returns analysis of the cut flower industry in Arevalo, Iloilo city. - Naquita, Gleny Macazar
This research study determines and analyses the costs and earnings from producing cutflower in Arevalo City. It covers the various cutflowers growers in Arevalo. The study seeks to test the validity of the following statements: a) The bigger the farm size of a cutflower grower the higher is the level of profit; b)The cutflower industry in Arevalo City is a profitable business. The study uses pure economic profit as a tool in analysing the status of the industry., The respondents were composed of 42 growers in Arevalo City. The data were gathered through direct interviews with the said growers. Moreover, the results of the study show that the cutflower industry in Arevalo was a profitable business. In the per dozen basis, Vanda growers gained the highest average PEP which amounted to P35.68. However, on the per farm basis, growers of Roses gained the highest PEP which is amounted to P190,755.07. On the costs side, Dendrobium and Roses gained the highest total costs which amounted to P69,959.71 and P38,814.01. This was highly comprised by total variable costs which was respectively 74 and 64 and 64 of the total costs. (p)The top three problems encountered by growers were labor, fungus/insects/pests and climate. These problems greatly affected the performance of the industry. (p)Based on the findings of the study, the researchers recommend two industry policies and one farm strategy. The policies were geared toward the reassessment of zoning in Arevalo, and on the creation of a better functional cooperative. The farm strategy recommended is called by the researchers as piping system. OF the total costs. The top three problems encountered by growers were labor, fungus/insects/pests and climate. These problems greatly affected the performance of the industry. Based on the findings of the study, the researchers recommend two industry policies and one farm strategy. The policies were geared toward the reassessment of zoning in Arevalo, and on the creation of a better functional cooperative. The farm strategy recommended is called by the researchers as piping system.